Nilai Tekanan serta Efisiensi Hidrolik Sistem Otomatis pada Proses Pengepresan Brondolan Menjadi Crude Palm Oil Unit Screw Press PT XY - Manahan Hutagalung (CV MEDAN TEKNO SOLUSI, 2023)
Screw press is a tool in the pressing unit at a palm oil mill which functions to extract oil from the fruit flesh by means of pressing, so that it has an important role in the palm oil industry. A screw press can also be interpreted as a tool used to extract oil from crushed fruit using pressure from a hydraulic press. The function of the screw press is to separate the crude oil from the fruit flesh and separate the fruit flesh from the seeds that have not been separated in the digester. Inside the Screw Press there is a worm screw which functions to move and press for palm oil so that the dregs are separated from the liquid, whether it is water or oil. This study aims to determine the amount of screw press pressure that works when pressing fiber and nuts on the screw press unit and determine the amount of hydraulic pressure efficiency for PT. XY. From the results of the study it was concluded that the screw press pressure on the press unit was 46 kg/cm2 and the hydraulic pressure was 55 kg/cm2, the oil extraction results were obtained with an efficiency of 85% hydraulic pressure.